ANALYSIS OF THE SCIENCE LEARNING PROCESS USING CANVA MEDIA ON STUDENT LEARNING PARTICIPATION IN GRADE IV ELEMENTARY SCHOOL - Arifial Fahla Nugraha; Devi Afriyuni Yonanda; Mohamed Nor Azhari Azman (Jurnal Cakrawala Pendas, 2025)
This study aims to analyze the use of Canva digital learning media in improving student learning participation in science subjects for grade IV elementary school. The method used is Classroom Action Research with two cycles including the planning stage, action implementation, observation, and reflection. Data were obtained through observation and student learning participation questionnaires. The results of the study showed a significant increase in student learning participation after the implementation of Canva media, both in terms of physical and psychological participation. In cycle I, the average student participation reached 65%, and increased to 85% in cycle II. The use of Canva has been proven to facilitate the presentation of material visually, attractively, and interactively so that it can increase students' focus and learning motivation. The conclusion of this study is that Canva media is effective in science learning to improve student learning participation in grade IV elementary school.